Triptolide Attenuates Vascular Calcification by Upregulating Expression of miRNA-204 - Yu-qiang Pei; Yong-qiu Zheng; Yao-dong Ding; Qi-xiang Xu; Di Cao; Ya-ning Wu; Rui Wang; Jia-xin Yang; Jing Liang; Qian Ma; Hai-long Ge (Frontiers Media S.A., 2021)
Background: Triptolide (TP), a naturally derived compound from Tripterygium wilfordii, has been proven effective in protecting against cardiovascular system, but the molecular mechanisms underlying its protective effects are poorly understood. In the current study, we sought to test the potential protective role of TP in the regulation of vascular calcification in a rat model and explore whether TP attenuates medial vascular calcification by upregulating miRNA-204.Methods: Vitamin D3 plus nicotine (VDN) was used to induce a vascular calcification (VC) model of rat aorta. Von Kossa and Hematoxylin-Eosin staining were applied to assess the degree of calcification of rat aortas. Calcium content and alkaline phosphatase activity were measured. Quantitative reverse-transcription polymerase chain reaction (qRT-PCR) was applied to quantify miRNA-204 expression. The localization of runt-related transcription factor-2 (RUNX2) and bone morphogenetic protein-2 (BMP2) expressions were detected by immunohistochemistry and western blotting.Results: Administration of TP greatly reduced vascular calcification in a dose-dependent manner compared with VC controls. The increase in ALP activity and calcium content was ameliorated by TP. Moreover, protein expression levels of BMP2 and RUNX2 were significantly reduced in calcified aortas. MiRNA-204 expression was increased in the TP-treated groups compared with VC controls and the effects of TP were reversed by the intravenous injection of miRNA-204-interfering lentivirus. However, the miRNA-204-overexpressing lentivirus had no additional effects on ALP activity, calcium content, BMP2 and RUNX2 expressions compared with those from TP group.Conclusion: TP inhibited BMP2 and RUNX2 expression and attenuated vascular calcification via upregulating the level of miRNA-204. TP appears to be a potential new therapeutic option for treating vascular calcification.